Pasividad en solución de fosfato de aceros inoxidables solidificados unidireccionalmente - Burgos, Rodrigo Elvio (2015)
Passivity of the stainless steel is attributed to the development of a protector film, formed by oxides on the metal surface. This film has semiconductor properties, and it is important for the understanding of corrosion phenomena.The objective of this work is to study the passive films formed in stainless steels samples solidified unidirectionally. The composition of the alloying elements in the samples are Fe-18Cr-10Ni-2Mo- 0,08C (sample A), Fe-18Cr-14Ni-8Mo-0,03C (sample C) y Fe-18Cr-10Ni-8Mo-0,08C (sample F), and determine the influence of the structure (equiaxed, columnar and columnar-to-equiaxed transition, CET) in the corrosion resistance, as well as investigate the relationship between the corrosion resistance and the size of the secondary dendritic arm spacing. For this are used potentiodynamic and galvanostatic techniques, Mott Schottky analysis and electrochemical impedance spectroscopy.The measurements were performed in Na2HPO40,5 M (pH = 9,2), at room temperature (25ºC).Potentiodynamic measurements indicate a passive region and a maximum current in the transpassive region. The galvanostatic measurements of the passive films indicate two plain of potential, due to chromium oxide and iron oxide, in which two transition times occur. The greater thickness of the iron oxide is in the equiaxed structures of sample F, which has the smallest dendritic spacing with respect to other two samples, given the same structure. Mott Schottky analysis shows that the passive film behaves as an n-type semiconductor in the potential range of -0.45 V to 0 V, with a density of-donor that varies according to the composition of stainless steel. It is also observed that the density-donor varies according to the type of structure for the same material.